Antimicrobial Activity of Piper aduncum subsp ossanum Essential Oil - Orlando A. Abreu,; Ileana Sánchez,; Jorge Pino,; Guillermo Barreto, (International Journal of Phytomedicine, 2015)
Plants are an important source for new antimicrobials. Piper aduncum L. (Piperaceae) is a medicinal plant use traditionally in South America and The Caribbean Basin. In Cuba, P. aduncum subsp. ossanum (C.CD.) Saralegui has ethnomedical reports as haemostatic, diuretic and, in urinary infection and skin infection. Ethanolic extract and essential oil obtained from this subspecie was tested by agar disc diffusion method against four strains of Escherichia coli (two uropathogenic clinical isolated), Staphylococcus aureus and Candida albicans. In all microorganisms a moderate or poor antimicrobial effect was exerted; but some activity was found against resistant sulfametoxazol or vancomicine E. coli strains. S. aureus and C. albicans were noted as the most sensitive microorganisms. Monoterpene camphor, present in the essential oil as main compounds could be responsible of the activity. These findings may support traditional use of this subspecie as antiseptic in Cuba.